LncRNA GAS5 suppresses the tumorigenesis of cervical cancer by downregulating miR-196a and miR-205 - Wenwu Yang; Li Hong; Xuexian Xu; Qin Wang; Jinling Huang; Li Jiang (Tumor Biology, 2017)
Growth arrest special 5 (GAS5) is a long non-coding RNA reported to function as an inhibitor in various tumors including cervical cancer. However, the molecular mechanism of GAS5 involved in cervical cancer progression remains far from being elucidated. The expression of GAS5, forkhead box protein O1 and phosphatase and tensin homolog was examined by quantitative reverse transcription polymerase chain reaction qRT-PCR. cell growth, invasion, and apoptosis were assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, colony formation assay, transwell invasion assay, and flow cytometry analysis, respectively. The interaction between GAS5 and miR-196a or miR-205 was confirmed by luciferase reporter assay, RNA immunoprecipitation assay, and qRT-PCR. Xenograft tumor experiments were performed to validate the biological role of GAS5 and its molecular mechanism in cervical cancer in vivo. GAS5 expression was decreased in cervical cancer tissues and cells. GAS5 overexpression suppressed cervical cancer cell proliferation, invasion, and apoptosis. GAS5 was able to directly bind to miR-196a and miR-205 to downregulate their expression. Moreover, GAS5 induced forkhead box protein O1 and phosphatase and tensin homolog expression by repressing miR-196a and miR-205, respectively. Exogenous expression of GAS5 hindered tumor growth in vivo by downregulating miR-196a and miR-205. Upregulation of GAS5 suppressed cell proliferation, invasion, and apoptosis of cervical cancer cells by downregulating miR-196a and miR-205, contributing to our understanding the pathogenesis of cervical cancer and development of long non-coding RNA–mediated clinical therapy against this disease.